Plasma in-Liquid Using Non-contact Electrodes: A Method of Pretreatment to Enhance the Enzymatic Hydrolysis of Biomass - Miranda, F. S.; Rabelo, S. C. [UNESP]; Pradella, J. G.C.; Carli, C. Di; Petraconi, G.; Maciel, H. S.; Pessoa, R. S.; Vieira, L. (Springer Nature, 2020)
Abstract: Dielectric Barrier Discharge (DBD) can be used to produce a large volume of non-thermal plasma at atmospheric pressure. Such plasmas are sources of highly reactive species (radicals, ozone, atoms, ions and excited molecules). Due to its characteristics, the DBD plasma can be applied for the pretreatment of lignocellulosic materials, in order to extract lignin that prevents the access to remained fermentable sugars in the biomass. In this context, an alternative method for pretreatment of lignocellulosic material in an in-liquid DBD plasma reactor using non-contact electrodes, working with atmospheric air, has been proposed. After the pretreatment, the solids were washed and submitted to enzymatic hydrolysis with a commercial enzyme complex, at 10 FPU/g of pretreated biomass and 50 g/L solids concentration (dry basis), for 72 h. The release of fermentable sugars was measured, comparing the samples obtained with and without plasma treatment. The highest sugar release was achieved using the plasma-in-liquid pretreatment in a single step, with glucose and xylose yields of 51.3 and 38.5%, respectively, after enzymatic hydrolysis. Thus, an effective pretreatment was developed to be applied to biomass such as: corn cob, sugarcane bagasse, bamboo, eucalyptus, etc., in order to reduce the environmental impact and, at the same time, produce biofuels. Graphic Abstract: [Figure not available: see fulltext.]
Keywords: Biofuels; Biomass; DBD plasma; Lignocellulosic materials; Pretreatment; Sugarcane bagasse